KUALITAS PELAYANAN PUBLIK: STUDI IZIN REKLAME PADA BADAN PENANAMAN MODAL KOTA BATU - Paula Aula Yenni Rukmana (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Abstract: Public Services which has been pursued by the government still get complaints from the society. The society complaints related to: quickness, accuracy, the officer ability, procedures, facilities and infrastructure, also transparency and efficiency. This issue also occurs in Batu, although the government has issued the regulation of advertisement with the Mayor Regulation No. 31 of 2009. The fact is, the advertisement which is appeared along the roadway is still a dilemma because some of them did not have the advertisement license yet. This research has a purpose to detect the Quality of the Public Services Advertisement Permit. The method used in this study is qualitative. The main data source is primary data, and supported by secondary data, with data collecting technique, through: observation, interviews and documentation, sampling technique selected through purposive sampling. The validity of the data using triangulation techniques. The results obtained in this research are, the Quality of Public Services Investment Board Batu particularly on billboard/advertisement regulation are appropriate with the requirement/demands of the society. There are two factors in the quality of public services. They are the supporting and inhibiting factors. Public Service Advertisement Permits can be good quality, because the service system based on the standard Operational Services, it is supported by communication factor, facilities, and infrastructure. Although it’s already at the stage of the improvement efforts, include: simplicity, security, openness, efficient and economical. Keywords: Quality, Public Service, license Abstrak: Pelayanan Publik yang selama ini diupayakan pemerintah masih mendapatkan keluhan dari masyarakat, diantaranya: kecepatan, ketepatan, kemampuan petugas sendiri, prosedur, sarana dan prasarana, keterbukaan dan efisiensi. Persoalan ini juga terjadi di Kota Batu, meskipun sudah mengeluarkan tata laksana perizinan reklame dengan Peraturan Walikota Batu Nomor 31 Tahun 2009. Fakta dilapangan reklame yang bermunculan di sepanjang ruas jalan raya masih dilematis karena masih ada yang belum memiliki perizinan reklame. Penelitian ini dilakukan dengan tujuan untuk mengetahui Kualitas Pelayanan Publik Izin Reklame. Metode digunakan dalam penelitian ini adalah kualitatif, sumber data utama adalah primer dan didukung data sekunder, dengan teknik pengumpulan data melalui: pengamatan, wawancara dan dokumentasi, teknik penentuan sampel dipilih melalui purposive sampling. Keabsahan data menggunakan teknik triangulasi. Hasil yang diperoleh dalam penelitian ini yaitu Kualitas Pelayanan Publik yang diberikan Badan Penanaman Modal Kota Batu khususnya pada perizinan reklame sudah sesuai dengan persyaratan/tuntutan dari masyarakat. Terdapat dua faktor dalam kualitas pelayanan publik yaitu faktor pendukung dan faktor penghambat. Pelayanan Publik Izin Reklame dapat berkualitas baik, dikarenakan sistem pelayanan berdasarkan Standar Operasional Pelayanan, hal tersebut didukung oleh faktor komunikasi, sarana dan prasarana. Meskipun sudah pada tahap upaya peningkatan, diantaranya: kesederhanaan, keamanan, keterbukaan, efisien dan ekonomis. Kata Kunci : Kualitas, Pelayanan Publik, Perizinan.